Energy Economics - Peter Zweifel (2020)
Access to energy resources, energy supply security, high and increasing prices of energy, lack of competition, slow market entry of renewables, insufficient investment in energy efficiency, and sluggish progress in reducing greenhouse gas emissions are all well-known issues and concerns characterizing energy markets. Yet, what are the possibilities of finding effective, efficient, and sustainable solutions to these problems? The fundamental claim of this book is that solutions cannot be found without an in-depth analysis of energy markets that acknowledges not only their physical and technological constraints but also their structural idiosyncrasies and the behavior of market participants.